If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 5x + -11 Reorder the terms: 9 + 7x = 5x + -11 Reorder the terms: 9 + 7x = -11 + 5x Solving 9 + 7x = -11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + 7x + -5x = -11 + 5x + -5x Combine like terms: 7x + -5x = 2x 9 + 2x = -11 + 5x + -5x Combine like terms: 5x + -5x = 0 9 + 2x = -11 + 0 9 + 2x = -11 Add '-9' to each side of the equation. 9 + -9 + 2x = -11 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = -11 + -9 2x = -11 + -9 Combine like terms: -11 + -9 = -20 2x = -20 Divide each side by '2'. x = -10 Simplifying x = -10
| -2p+14=-32 | | 8a+2=14 | | 8b+2=14 | | 88-36= | | -6(2x+5)=4x-14 | | 2(x-1)=-9 | | 2x-3(x+4)=-4 | | -(7y-8)-(-6y-4)=9 | | 5x+3y=p | | -2p+14=-35 | | (y-3)-(y+9)=5y | | 4p-2=5-7p+6p | | 2b-9=7+7b | | 5(x-3)=-3(x-11) | | .3333333n+3=n+2 | | 10a-7=101+a | | 49=8x-7 | | 4(x+2)=9+x | | 8r+2=34 | | 0=(x*x)-x-5 | | -2(3s-3)-6=-3(6s+7)-3 | | 8r^2=6r-1 | | 8-2x+3x^2=0 | | =5x+2 | | X+7=(x*x)+2 | | y/z=9 | | F(x)=x^5-9x^3+27x | | -46+78=-60 | | 2x(x-10)+4=6x+2 | | 5/x=11/3 | | 5x-x/3=85 | | 6x+2z=6+5y |